The Impact of Gender-Specific Cultural Knowledge and English Proficiency on the Reading Comprehension of Saudi EFL Undergraduates - Shah, Usman (Register Journal, 2024)
The present study aimed to examine the impact of gender-specific background knowledge and language proficiency on reading comprehension among Saudi EFL undergraduate students at Majmaah University. The primary method of data collection was quantitative, involving two culturally distinct texts – one familiar and one unfamiliar to the participants. The research design included 120 second-year undergraduate students (60 males and 60 females) majoring in English at Majmaah University. The study employed a quantitative approach, with statistical analyses conducted utilizing regression models to explore the relationships between gender, language proficiency, and reading comprehension scores. The findings revealed several gender-related factors influencing reading comprehension, including social and cultural influences that may affect students’ understanding of texts. These findings suggest that teachers can modify curricula and instructional methods to account for these factors, while teacher training programs should incorporate elements of language development and cultural competency. Furthermore, promoting inclusivity in education can be achieved by revising policies and implementing tailored student support programs. Future research is required to investigate additional relevant factors and conduct cross-cultural comparisons. In particular, further studies should investigate the effects of multicultural reading materials currently used in EFL instruction on undergraduate students' reading comprehension and language proficiency.